Investigating the effects of Lonchocarpus Cyanencens Aqueous Leaf Extracts on the Histology of the Cardiovascular System in Normal Albino Wistar Rats - Onyeije Benson Peter*1, Innih Silvanus Orlu2 (Sokoto Journal of Medical Laboratory Science)
The shrub tree Lonchocarpus cyanescens is one of the herbal remedies traditionally used in Nigeria to promote human health. In the western part of the nation Nigeria, it is used to treat d i a b e t e s m e l l i t u s . I n v e s t i g a t i n g t h e histomorphological activities of an aqueous extract of Lonchocarpus cyanescens leaf on the cardiovascular status of normal Wistar albino rats was the purpose of this investigation. Thirty-five rats in all were split up into seven groups of five rats each: Group A was designated as the control group. Group B was given an aqueous extract of L. Cyanencens containing 200 mg/kg, Group C was given 500 mg/kg, Group D was given 1000 mg/kg, Group E was given 2000 mg/kg, Group F and H were given 3500 mg/kg and 5000 mg/kg of the extract, respectively. The rats had 42 days of therapy before being cervically dislocated while sedated with ether. The rat's heart was quickly removed, preserved for 72 hours in 10% buffered formalin, and then histologically processed and stained with eosin and hematoxylin. According to histological findings, all treated groups experienced mild vascular events with intact interstitial spaces and myocardial bundle arrangement in the cardiovascular system as a result of graded doses of Lonchocarpus cyanescens aqueous extracts. These extracts also activated the heart's local immune system, causing endothelial cell activation and lymphocytosis (induction fraction). A more intense action was elicited by the lower doses, peaking at 1000 mg/kg. But there were no harmful consequences, affirming the safety of the extract and its potential for treatment of cardiovascular diseases.